Leaf compatible "eco-friendly" temperature sensor clip for high density monitoring wireless networks. Issue 1 (15th February 2017) - Palazzari, Valeria; Mezzanotte, Paolo; Alimenti, Federico; Fratini, Francesco; Orecchini, Giulia; Roselli, Luca
Abstract : This paper describes the design, realization, and application of a custom temperature sensor devoted to the monitoring of the temperature differential between the leaf and the air. This difference is strictly related to the plant water stress and can be used as an input information for an intelligent and flexible irrigation system. A wireless temperature sensor network can be thought as a decision support system used to start irrigation when effectively needed by the cultivation, thus saving water, pump fuel oil, and preventing plant illness caused by over-watering.